E-086 Unilateral cerebral vasoconstriction following combined carotid neurosurgical and endovascular carotid revascularization. (22nd July 2019) - Sheikhi, L; Tsai, J; Bain, M; Toth, G
Abstract : Introduction: Reversible cerebral vasoconstriction syndrome (RCVS) can occur spontaneously or may be a secondary response. RCVS is rarely reported in literature following carotid revascularization and thought to be a possible result of chronic cerebral hypoperfusion with disturbance of cerebral autoregulation. There is no standard treatment for this condition. Here we report occurrence and management of cerebral vasoconstriction following unique combined neurosurgical and endovascular carotid revascularization for symptomatic carotid occlusion. Methods: We review a patient's clinical and imaging characteristics following carotid artery revascularization. Results: A female patient in her 70 s with history of hypertension, controlled type 2 diabetes mellitus, and current smoker presented with recurrent episodes of transient left sided limb shaking. She was found to have a right internal carotid artery (ICA) occlusion at the cervical origin with a non-flow limiting 40% stenosis of the left ICA associated with an acute infarct in the right frontal white matter. A diagnostic cerebral angiogram confirmed the occlusion of the right ICA with limited and delayed retrograde filling from the vertebrobasilar system via the right posterior communicating artery and smaller collateral contribution via right external carotid to ophthalmic artery. Notably, there was no anterior communicating artery for contralateral cross-filling. She had several outpatient visits and hospital admissions for hypotensive episodes associated with recurrent stereotypic symptoms. Repeat imaging demonstrated overall small stroke burden and no hemorrhage. Upon careful discussion and review of possible options, a combined neurosurgical-endovascular carotid revascularization was performed with endarterectomy of an occlusive plaque involving the distal common carotid to the proximal ICA, and direct mechanical thrombectomy with aspiration and stentriever of the cervical ICA to the terminus. Additional angioplasty and stenting of proximal petrous ICA segment was performed via femoral access after closure of the surgical site. She clinically was doing well until 5 days post-operatively, when she developed recurrent symptoms. Imaging showed small new ischemic strokes without hemorrhage. Continuous video-EEG monitoring was negative for seizures. Transcranial doppler monitoring over the next few days demonstrated worsening velocities, with a repeat angiogram confirming severe focal segmental irregularities isolated to the right anterior territory. The surgical and stenting site remained widely patent. Her vasospasm was successfully treated with intra-arterial verapamil with improvement in vessel caliber and clinical symptoms. Conclusions: Post carotid revascularization cerebral vasoconstriction may be an unusual cause of clinical worsening after revascularization for chronic carotid stenosis or occlusion. Intra-arterial treatment with verapamil can be a safe and effective mode of therapy. Disclosures: L. Sheikhi: None. J. Tsai: None. M. Bain: 2; C; Stryker. 4; C; Rebound Therapeutics. G. Toth: None.